Levels of narcissism in educators and their effects on the tutorial function. - Cerna Dorregaray, Orlando (2017)
The present investigation wishes to know the relation that exists between the narcissistic personality structure of the educators with the performance of their tutorial function. It is a descriptive correlational study, which describes the levels of narcissism in educators and relates them to the perception that students have of the tutorial action carried out by their tutors. 172 teachers were evaluated, 84 of them tutors and 3,765 high school students from nine religious schools in Peru. An important aspect of this study is that there is a lot of research on tutoring depending on the student, but not from the perspective of the educator's personality, as if it were denied and was not linked to educational work. What was sought in the study is to demonstrate the importance of the educator's personality variable in the tutorial actions that educators perform; especially the levels of narcissism of the educators and how these are related to the students' perception of the individual, group tutorial action and with the parents.